Begonia subvillosa, new running wild Begonia in Cibodas Botanical Gardens and naturalized prediction - Muhammad Efendi; Abidin Ibrahim; Yani Suryani; Salma Salsabila (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2022)
.